Basic Electrical Welding Training at the Markaz Hadist Bilal Bin Rabah Islamic Boarding School Tangerang - Rizal, Syaiful; Sekarsari, Kartika; Rozak, Ojak Abdul (Jurnal Pengabdian Masyarakat Formosa, 2024)
A welding machine is a tool for welding thin and thick plates which can be used to make house fences, shelves, tables, chairs and so on. The community service, which is packaged in such a way and carried out at the Tahfiz Markaz Hadits Bilal bin Rabah Aliyah Legok Islamic Boarding School, aims to provide welding training using electric welding to the students so that when they enter society, they become productive humans. Additionally, they can work independently. This community service activity made all participants who participated in PkM activities feel enthusiastic about participating from start to finish. They also tried to practice welding themselves under the guidance of lecturers and students.